Digital Enrollment and Survey Response of Diverse Kidney Transplant Seekers in a Remote Trial (KidneyTIME): An Observational Study - Rhys Mendel; Jing Nie; Maria Keller; Yasmin Aly; Harneet Sandhu; Matthew Handmacher; Liise Kayler (Kidney and Dialysis)
Introduction: The feasibility of enrolling and retaining diverse kidney transplant (KT) seekers in remote studies is sparsely reported. Aims: This study examined the use of a mobile communication strategy to enroll and retain participants within a clinical trial of an automated digital intervention to promote self-learning for kidney transplant access. Materials and Methods: Adult KT-seekers were identified from an administrative database at a transplant center and recruited by email or text supplemented by verbal prompts. Multivariable logistic regression was used to explore participant- and study-level characteristics associated with enrollment and response rates. Results: Between April 2022 and June 2023, 743 patients were invited to participate, and 422 were enrolled. Enrollers were more likely to be younger (aOR 1.02; p < 0.001). Early enrollment was associated with text message invitation (OR 2.69, p ≤ 0.014). Survey completion at 1 month was similar across patient sociodemographic, clinical, and study characteristics; however, participants self-reporting Black race were underrepresented at month 6 (OR 0.55, p = 0.015) and month 12 (aOR 0.37, p = 0008), and males were underrepresented at month 12 (aOR 0.45, p = 0.028). Conclusion: Mobile communication methods are viable for enrolling diverse KT-seeking patients and collecting survey data remotely. More work is needed to learn how to best recruit older people and retain diverse groups long-term.